PERAN TATA KELOLA PERUSAHAAN YANG BAIK DALAM MEMODERASI TEKANAN PEMANGKU KEPENTINGAN YANG KOMPREHENSIF TERHADAP KUALITAS LAPORAN KEBERLANJUTAN - Muanifah, Suciati; Holiawati; Suripto (Faculty of Economics and Business University of Mataram, 2023)
Sustainability reporting serves as a means to communicate a company's performance across environmental, social, and governance aspects, vital for stakeholders. This study investigates how corporate governance influences the relationship between stakeholder pressures and sustainability report quality among Indonesia Stock Exchange-listed firms from 2019 to 2021. Using quantitative methods and data analysis in Microsoft Excel and Eviews 9, the research analyzed 49 samples from 864 companies. The results suggest that stakeholder pressures collectively impact sustainability report quality. However, the effectiveness of Board of Commissioners' supervision in Good Corporate Governance (GCG) does not moderate this relationship in the Consumer-Oriented Industry, whereas it does moderate the relationship in the Environmentally Sensitive Industry. In summary, the Consumer-Oriented Industry has a limited impact on sustainability report quality, while the Environmentally Sensitive Industry has a significant impact.